2011
DOI: 10.1016/j.jacc.2010.08.641
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Consumption and Risk of Atrial Fibrillation

Abstract: Results of this meta-analysis suggest that not consuming alcohol is most favorable in terms of AF risk reduction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
145
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 259 publications
(161 citation statements)
references
References 42 publications
8
145
1
7
Order By: Relevance
“…These indirect effects of ethanol may be arrhythmogenic, particularly in individuals prone to AF such as patients with focal AF. A meta-analysis supported these pathophysiologic expression and showed that habitual heavy alcohol drinking was associated with an increased risk of AF [21]. In our study there was no relationship between alcohol intake and late recurrence of AF.…”
Section: Discussionsupporting
confidence: 74%
“…These indirect effects of ethanol may be arrhythmogenic, particularly in individuals prone to AF such as patients with focal AF. A meta-analysis supported these pathophysiologic expression and showed that habitual heavy alcohol drinking was associated with an increased risk of AF [21]. In our study there was no relationship between alcohol intake and late recurrence of AF.…”
Section: Discussionsupporting
confidence: 74%
“…Several reports4, 5, 20 have described the mechanism of how the consumption of alcohol causes AF. First, there is a link between chronic alcohol abuse and alcoholic cardiomyopathy,4, 21 which possibly leads to cardiac arrhythmias such as AF.…”
Section: Discussionmentioning
confidence: 99%
“…The population with AF will significantly increase in the future with the increasingly aging society 1. In addition to the well‐known risk factors, including hypertension, diabetes mellitus, cardiovascular disease, obesity, metabolic syndrome, and chronic kidney disease, lifestyle characteristics such as alcohol consumption are significantly linked to the incidence and/or prevalence of AF 2, 3, 4, 5. Although catheter ablation (CA) is standard therapy for patients with AF,6, 7, 8 the impact of alcohol consumption on the outcomes of CA has not been discussed.…”
Section: Introductionmentioning
confidence: 99%
“…Lightto-moderate drinking was observed as generally beneficial in minimising the risk of these cardiovascular events, even after accounting for incident MI, except for atrial fibrillation and hypertension [121,122]. Heart failure, for example, is a complex syndrome with multiple causes including coronary heart disease, endomyocardial fibrosis, hypertension, myocardial infarction, obesity and type 2 diabetes [123,124].…”
Section: Relationship Between Alcohol and Individual Cardiovascular Dmentioning
confidence: 99%
“…The relationship between atrial fibrillation, a common chronic cardiac arrhythmia, and alcohol appears to be a casual, linear and dose-response relationship, which may reflect alcohol-induced electrophysiological changes in atrial cells [121,122,[125][126][127]. Atrial fibrillation is closely associated with both heart failure and hypertension.…”
Section: Atrial Fibrillationmentioning
confidence: 99%